Green Product In Micro Small Medium Enterprises (MSME) - Dewi Nusraningrum; Sugiyono Sugiyono; Wei-Loon Koe (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service is an activity related to community economic empowerment through socialization and training in implementing green product entrepreneurial production strategies. The problem that arises in the production of green products is the limitation of knowledge that causes the quality of local products to be unable to compete in national, regional, and international markets. In order to support community service, community economic empowerment efforts about green products will help small and medium enterprises to know how to develop the production of competing for green products. For this reason, this activity will provide assistance and training in green product production strategy skills, so that later partners are able to become independent and have a production strategy. These skills in addition to being beneficial to themselves will at least help reduce the economic burden of the family by earning income from the production of green products developed. The outcome of this activity is (1) the Development of green product knowledge. (2) Assistance of participants in transforming into green business-oriented businesses by involving local communities to produce green products.